A two-stage aging process method for a thin-walled aluminum alloy photovoltaic frame

CN122879624APending Publication Date: 2026-10-09CHUZHOU RUIDA NEW ENERGY MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611220290.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-12
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0005]本发明的目的就是为了弥补现有技术的不足,提供了一种薄壁铝合金光伏边框双级时效工艺方法,通过测定装炉密度系数并根据装炉密度等级动态调整三阶段时效工艺参数,旨在解决因装炉密度变化导致的批次间性能不稳定问题

Benefits of technology

[0023]一、本发明通过测定装炉密度系数并划分装炉密度等级,为不同装炉状态匹配对应的三阶段时效工艺参数,使各阶段温度、保温时间及升降温速率与装炉密度形成联动适配,可有效补偿不同装炉密度下热屏蔽效应引发的热滞后差异,消除炉膛内热场分布不均对型材析出进程的影响,缩小同炉不同位置及不同生产批次间的力学性能波动,显著提升产品性能一致性与批次稳定性,解决传统固定时效参数适配性差的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122879624A_ABST
    Figure CN122879624A_ABST
Patent Text Reader

Abstract

The application discloses a kind of double-stage aging process methods of thin-walled aluminum alloy photovoltaic frame, it is related to aluminum alloy heat treatment technical field, the method is first determined the loading density coefficient of aging furnace, according to this, loading state is divided into different density grades, then the three-stage aging process parameters of corresponding grade are matched, the temperature, holding time and heating rate of each stage are all linked with the loading density and form matching relationship, finally, aging treatment is completed according to the determined process parameters.The present application can effectively compensate the thermal hysteresis effect under different loading densities, reduce the performance fluctuation between the same furnace and batch, improve the consistency of product performance, optimize the precipitated phase organization state, balance the material strength and corrosion resistance, and is suitable for the industrialized aging production of thin-walled 6 series aluminum alloy photovoltaic frame.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of aluminum alloy heat treatment technology, specifically to a two-stage aging process for thin-walled aluminum alloy photovoltaic frames. Background Technology

[0002] Aluminum alloy frames for photovoltaic modules are typically made from 6-series Al-Mg-Si alloys through extrusion molding, with wall thicknesses generally ranging from 0.8 to 2.5 mm. Aging heat treatment is a key process for these thin-walled profiles to obtain the required mechanical properties. Currently, the single-stage T5 aging process is commonly used in industrial production, which involves holding the material at a temperature of 180-185℃ for 5-6 hours.

[0003] Several patents have proposed improved solutions for the aging treatment of aluminum alloys. Patent publication number CN102825092A discloses a production process for hard aluminum alloy profiles, employing continuous extrusion combined with a two-stage aging heat treatment. The first-stage aging temperature is 450-520℃ for 30-120 minutes, and the second-stage aging temperature is 150-250℃ for 2-12 hours. This patent targets Al-Si-Cu series hard aluminum alloys, and its first-stage aging temperature falls within the solution treatment temperature range rather than the aging temperature range. Furthermore, the alloy system it targets is completely different from 6-series aluminum alloys. Another patent publication number CN106756669B discloses an aluminum alloy heat treatment process using artificial aging at 190-200℃ for 2 hours, followed by a second aging treatment at 160-170℃ for 10 hours for defective products. This two-stage aging solution is used as a remedial measure for rework of defective products, not a proactive design for the normal production of thin-walled profiles.

[0004] In the aforementioned existing technologies, the aging process uses fixed temperature and time parameters, which are independent of the actual loading state of the profiles in the aging furnace. However, in actual production, the loading density (the proportion of profiles in a unit furnace volume) varies significantly between different batches in the same aging furnace. The loading density directly affects the heat flow field distribution within the furnace. The denser the loading, the stronger the thermal shielding effect between the profiles, the lower the actual heat flux reaching the profile surface, and the slower the equivalent heating rate. Under the same set of fixed aging parameters and different loading densities, the actual thermal history experienced by the profiles differs, leading to significant fluctuations in the mechanical properties of profiles from different batches or even different locations within the same furnace. Summary of the Invention

[0005] The purpose of this invention is to overcome the shortcomings of the prior art and provide a two-stage aging process method for thin-walled aluminum alloy photovoltaic frames. By measuring the furnace loading density coefficient and dynamically adjusting the three-stage aging process parameters according to the furnace loading density level, this invention aims to solve the problem of batch-to-batch performance instability caused by changes in furnace loading density.

[0006] To solve the above-mentioned technical problems, the present invention provides the following technical solution: a two-stage aging process for thin-walled aluminum alloy photovoltaic frames, the method comprising the following steps:

[0007] Step 1: Measure the furnace charge density coefficient ρ. ,in The ratio is the sum of the projected areas of all thin-walled aluminum alloy photovoltaic frame profiles in the aging furnace on a plane perpendicular to the length of the furnace chamber. L is the effective length of the furnace chamber, W is the effective width of the furnace chamber, and H is the effective height of the furnace chamber. This ratio is used to quantitatively characterize the furnace loading density and provide a basis for subsequent process parameter adjustments.

[0008] Step 2: Based on the charging density coefficient ρ, the charging state is divided into three levels: low-density charging, medium-density charging, and high-density charging. ρ≤0.30 is low-density charging, 0.30<ρ≤0.48 is medium-density charging, and ρ>0.48 is high-density charging.

[0009] Step 3: Determine the three-stage aging process parameters based on the furnace loading status level. The three-stage aging process includes the first stage of low-temperature pre-aging, the second stage of medium-temperature main aging, and the third stage of short-time regression. The temperature and time of the first stage of low-temperature pre-aging are positively correlated with the furnace loading density coefficient ρ. The temperature and time of the second stage of medium-temperature main aging are negatively correlated with the furnace loading density coefficient ρ, and positively correlated with the furnace loading density coefficient ρ. The temperature of the third stage of short-time regression is 180-190℃, and the time is positively correlated with the furnace loading density coefficient ρ and does not exceed 22 minutes. Through the above linkage relationship, the parameters of each stage are dynamically matched with the furnace loading density to compensate for the thermal hysteresis differences under different furnace loading densities.

[0010] Step four: Perform a three-stage aging treatment on the thin-walled aluminum alloy photovoltaic frame profile according to the determined process parameters.

[0011] Furthermore, in step two, the process parameters for low-density loading are: first stage temperature 90℃, time 5.0h, second stage temperature 160℃, time 3.0h, and third stage temperature 185℃, time 12min.

[0012] The process parameters for medium-density loading are: first stage temperature 95℃, time 6.0h, second stage temperature 158℃, time 3.5h, and third stage temperature 185℃, time 15min.

[0013] The process parameters for high-density loading are: first stage temperature 100℃, time 7.5h; second stage temperature 155℃, time 4.5h; third stage temperature 185℃, time 18min. The above three process parameters correspond to the optimal aging regime under three loading density levels, so that the profiles under different loading densities can reach similar precipitation states.

[0014] Furthermore, in step two, the temperature of the first stage low-temperature pre-aging is 80-105℃ and the time is 4-8h, and the temperature of the second stage medium-temperature main aging is 150-168℃ and the time is 2.5-5h.

[0015] Furthermore, in step two, the heating rate of the first stage low-temperature pre-aging is 1.5-2.5℃ / min. The heating rate of the first stage low-temperature pre-aging is negatively correlated with the furnace charge density coefficient ρ. When the furnace charge density is high, the heating rate is reduced to suppress the asynchronous precipitation inside and outside caused by excessive temperature difference in the profile cross section.

[0016] Furthermore, in step two, the first stage heating rate between the first stage low-temperature pre-aging and the second stage medium-temperature main aging is 0.5-1.2℃ / min. The first stage heating rate is negatively correlated with the furnace density coefficient ρ. The gradient heating makes the temperature field of the profile cross section uniform before entering the next aging stage, ensuring that the precipitation process of each part is synchronized.

[0017] Furthermore, in step two, the second-stage heating rate between the second-stage medium-temperature main aging and the third-stage short-time regression is 0.8-1.5℃ / min, and the second-stage heating rate is negatively correlated with the furnace charge density coefficient ρ.

[0018] Furthermore, in step two, after the short-term regression in the third stage, the temperature is reduced to below 100℃ at a rate of 0.5-1.8℃ / min. The cooling rate is negatively correlated with the furnace loading density coefficient ρ. Gradient cooling suppresses the tendency of continuous distribution of grain boundary precipitates and improves corrosion resistance.

[0019] Furthermore, in step one, the furnace loading density coefficient ρ is automatically calculated by the control system after scanning the profile outline by an optical ranging sensor array. The furnace loading density coefficient is obtained in real time through automatic measurement by the sensor, without the need for manual intervention.

[0020] Furthermore, in step one, the furnace loading density coefficient ρ is calculated by the control system after the number of profiles, the cross-sectional profile dimensions of a single profile, and the effective dimensions of the furnace are manually input.

[0021] Furthermore, in step one, the wall thickness of the thin-walled aluminum alloy photovoltaic frame profile is 0.8-2.5mm, and the material of the thin-walled aluminum alloy photovoltaic frame profile is 6-series aluminum alloy. This wall thickness range corresponds to the actual specifications of the photovoltaic frame profile, and 6-series aluminum alloy is the precipitation-strengthened alloy system suitable for this solution.

[0022] Compared with existing technologies, this two-stage aging process for thin-walled aluminum alloy photovoltaic frames has the following advantages;

[0023] I. This invention measures the furnace loading density coefficient and classifies the furnace loading density levels to match corresponding three-stage aging process parameters for different furnace loading states. This enables the temperature, holding time, and heating / cooling rates of each stage to be linked and adapted to the furnace loading density. This can effectively compensate for the thermal hysteresis differences caused by the thermal shielding effect under different furnace loading densities, eliminate the impact of uneven thermal field distribution in the furnace on the profile precipitation process, reduce the mechanical property fluctuations between different locations in the same furnace and between different production batches, significantly improve product performance consistency and batch stability, and solve the problem of poor adaptability of traditional fixed aging parameters.

[0024] Second, this invention adopts a three-stage aging system of low-temperature pre-aging, medium-temperature main aging, and short-time regression. The low-temperature stage induces the formation of uniform and fine nucleation cores, the medium-temperature stage promotes the stable precipitation and growth of strengthening phases, and the short-time regression stage optimizes the size distribution and morphology of precipitated phases. Under the premise of ensuring that the strength of the profile meets the requirements for use, it can improve the plasticity and corrosion resistance of the material. With the controlled heating and cooling rates of each stage, it can avoid the problem of asynchronous precipitation caused by excessive temperature difference in the cross section of thin-walled profiles, and further ensure the uniformity of the microstructure of the profile cross section.

[0025] Other advantages, objectives and features of the invention will be set forth in part in the description which follows, and in part will be apparent to those skilled in the art from the following examination or study, or may be learned from the practice of the invention. Attached Figure Description

[0026] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the accompanying drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are merely some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without any creative effort.

[0027] Figure 1 This is a flowchart of the process method of the present invention;

[0028] Figure 2 This is a schematic diagram of the dynamic adjustment of the three-stage process parameters of the present invention. Detailed Implementation

[0029] To further illustrate the technical means and effects of the present invention in achieving its intended purpose, the following detailed description of the specific implementation methods, structures, features, and effects of the present invention, in conjunction with the accompanying drawings and preferred embodiments, is provided below.

[0030] Example 1

[0031] See Figure 1This embodiment describes a thin-walled aluminum alloy photovoltaic frame of a certain type, made of 6063 aluminum alloy, with a profile wall thickness of 1.4mm, an L-shaped cross-section, and a single-piece length of 6m. The effective length L of the aging furnace chamber is 8m, the effective width W is 2m, and the effective height H is 1.8m.

[0032] During this batch of furnace loading, the profiles are stacked layer by layer on the material rack, with the length of the profiles parallel to the length of the furnace chamber. After loading, an optical rangefinder sensor array mounted inside the furnace door scans the contours of the material rack and profiles. The sensor array consists of multiple sets of laser displacement sensors arranged in a grid pattern, which can acquire the projected contour data of the profiles in the direction perpendicular to the length of the furnace chamber. After receiving the sensor data, the control system fits the outer contour of all profiles in the projection plane and calculates the sum of the projected areas. This measurement It is 2.96m².

[0033] The control system retrieves the effective dimensions of the furnace and automatically calculates the loading density coefficient ρ according to a preset program. Calculations show that the density (ρ) for this batch is 2.96 ÷ (8 × 2 × 1.8), which is 2.96 ÷ 28.8, resulting in 0.31. This value falls within the range of 0.30 to 0.48, and the control system automatically classifies this batch as a medium-density loading grade.

[0034] Based on the medium-density loading level, the control system retrieves the corresponding three-stage aging process parameters from the process database. These parameters are established based on extensive preliminary experimental data and numerical simulation results and are built into the system; the specific settings are as follows.

[0035] The first stage is low-temperature pre-aging. The core objective of this stage is to induce the formation of high-density, small-sized atomic clusters or GP regions at a lower temperature, providing nucleation sites for effective precipitation in the subsequent main aging stage. Since the furnace packing density for this batch is moderate, the furnace thermal shielding effect is adequate. To balance efficiency and cross-sectional temperature uniformity, the target temperature for the first stage is set at 95℃, and the holding time is set at 6.0 h. The heating process is controlled, with a heating rate set at 2.0℃ / min. A slower heating rate helps reduce the temperature difference between the inside and outside of the thin-walled profile cross-section, preventing inconsistent precipitation processes between the profile surface and core due to excessively rapid heating. The control system adjusts the heating element output power to control the heating slope. The holding time begins once the average temperature fed back by multiple thermocouples near the profile in the furnace reaches 95℃.

[0036] After the first stage of heat preservation is completed, the heating phase transitions to the second stage of medium-temperature aging. To ensure a smooth transition and rehomogenize the temperature field of the profile cross-section at a higher temperature, the heating rate for this stage is set to 0.8℃ / min. The control system adjusts the furnace temperature setpoint to the target temperature of 158℃ for the second stage and controls the heating power to ensure the furnace temperature rises at the predetermined rate.

[0037] The second stage is the medium-temperature primary aging process. This is a crucial stage for significant precipitate growth and rapid increase in alloy strength. Considering the characteristics of this batch of medium-density furnace-loaded alloys, the target temperature for the second stage is set at 158℃, and the holding time is set at 3.5 hours. This temperature and time matching aims to promote uniform precipitation and growth of the strengthening phase with appropriate energy input, avoiding performance degradation due to coarsening of the precipitates caused by excessively high temperatures or excessively long holding times. Once the furnace temperature reaches 158℃, the holding timer is activated.

[0038] After the second stage of heat preservation is completed, the heating stage begins again, targeting the return temperature of the third stage. The heating rate for this stage is set at 1.2℃ / min, and the control system adjusts the furnace temperature target to 185℃.

[0039] The third stage is a short-term regression treatment. This stage involves a brief period of high-temperature treatment to induce partial dissolution of the small-sized, metastable precipitates formed during the previous aging process. Simultaneously, it makes the size distribution and morphology of the remaining precipitates more rational, effectively improving the material's plasticity or toughness while maintaining its strength. In this embodiment, the third-stage temperature is set to 185℃, and the holding time is set to 15 minutes. See also... Figure 2 After the insulation period ends, the controlled cooling phase begins.

[0040] The cooling process is equally important. The control system shuts off the heating power and, according to the preset cooling curve, starts the circulating fan and adjusts the damper opening to control the cooling rate. In this embodiment, the cooling rate is set to 1.2℃ / min, allowing the profile to slowly cool from 185℃ to below 100℃. A stable cooling rate can suppress the continuous precipitation and excessive growth of the strengthening phase at the grain boundaries, which plays a positive role in ensuring the corrosion resistance of the profile. When the temperature feedback from the temperature measuring point is below 100℃, the control system indicates that the aging process is complete, and the furnace door can be opened to remove the profile.

[0041] To objectively evaluate the effectiveness of the process scheme in this embodiment, mechanical properties and microstructure tests were conducted on the profiles after the above-described process. Within the same furnace batch, samples were taken from nine locations at the upper, middle, and lower parts of the furnace (front, middle, and rear). The sampling method involved cutting tensile specimens from the profiles, processing them according to GB / T16865 standard, and conducting room temperature tensile tests on a universal testing machine according to GB / T228.1 standard.

[0042] Test results showed that the tensile strength values ​​at the nine test points ranged from 242 MPa to 249 MPa, with a difference of 7 MPa between the maximum and minimum values; the specified plastic elongation strength ranged from 216 MPa to 223 MPa, with a range of 7 MPa; and the elongation after fracture ranged from 11.5% to 12.8%. These data indicate that the range of mechanical property fluctuations in profiles at different locations within the same furnace batch was significantly narrowed, demonstrating good consistency. Transmission electron microscopy revealed that the precipitates in the matrix were needle-like or rod-like, uniformly dispersed, and the precipitates at the grain boundaries were discontinuously distributed, with no obvious continuous chain-like precipitates observed. This is consistent with the obtained mechanical properties and expected corrosion resistance.

[0043] This embodiment automatically measures the furnace loading density coefficient, quantifies the actual furnace loading state into a specific value, and determines the batch as medium density based on this value, dynamically applying a matching three-stage aging parameter combination. The entire process requires no manual judgment or intervention, achieving precise setting of process parameters and effectively solving the problem of batch-to-batch performance instability caused by changes in furnace loading density under traditional fixed parameter modes.

[0044] Example 2

[0045] This embodiment refers to another production batch, where the profile material, specifications, and aging furnace are the same as in Embodiment 1. To improve production efficiency, the furnace loading in this batch has been increased, and the profile arrangement is more dense.

[0046] After the furnace is loaded, the optical rangefinder array scans and calculates the sum of the projected areas of the profiles. The volume is 4.18 m². The control system calculates the furnace loading density coefficient ρ = 4.18 ÷ 28.8, which is 0.50, > 0.48. Based on this, the control system classifies this batch as a high-density loading level.

[0047] The system calls upon the three-stage aging process parameters corresponding to the high-density furnace loading. Due to the high loading density, the thermal shielding effect between profiles is significantly enhanced, increasing the resistance to heat flow reaching the surface of each profile, and making the lag in temperature lag between the profile core and the furnace gas temperature more pronounced. To compensate for this thermal lag effect, the process parameters are adjusted accordingly.

[0048] The target temperature for the first stage of low-temperature pre-aging was increased to 100°C, and the holding time was extended to 7.5 hours. The higher temperature and longer holding time compared to Example 1 were to provide sufficient and effective nucleation sites for subsequent precipitation, overcoming the adverse effects of slow heat transfer under high-density loading. The heating rate was set to 1.8°C / min, lower than that for medium-density loading, to minimize the cross-sectional temperature difference caused by dense loading and ensure that the nucleation process occurs synchronously across the entire cross-section.

[0049] After the first stage of heat preservation, the temperature was increased to the target temperature of 155℃ for the second stage at a rate of 0.7℃ / min. The target temperature for the second stage of medium-temperature main aging was set at 155℃, slightly lower than 158℃ in Example 1, and the heat preservation time was extended to 4.5 hours. The logic behind this adjustment is that when the furnace is loaded with high density, the actual heat transfer efficiency of the furnace atmosphere is reduced, but the profile itself has a very large heat capacity, and once heat is transferred, its temperature maintenance ability is also strong. By adopting a slightly lower but longer heating regime, it is possible to ensure sufficient total heat input and allow the strengthening phase to precipitate and grow steadily under milder conditions, avoiding local overheating that could lead to performance differentiation.

[0050] After the second stage of heat preservation, the temperature is increased to 185℃ at a rate of 1.0℃ / min. The third stage, a short-term reheat, also uses a temperature of 185℃, but the holding time is extended to 18 minutes. This longer reheat time aims to more fully dissolve some of the excessively fine and unstable precipitates that may form under high-density nucleation conditions, optimizing the size distribution of the precipitates. After the heat preservation period, a controlled cooling rate of 1.0℃ / min is set to allow the profile to cool smoothly to below 100℃.

[0051] The same sampling and performance testing were performed on the profiles processed in this batch. The tensile strength of the nine sampling points ranged from 237 MPa to 248 MPa, with a range of 11 MPa; the specified plastic elongation strength ranged from 211 MPa to 224 MPa, with a range of 13 MPa; and the elongation after fracture ranged from 10.8% to 12.3%. Despite the increased furnace loading density, by adjusting the process parameters dynamically matched to the furnace loading conditions, the performance fluctuations within the same furnace batch were still controlled within a narrow range, and the product performance consistency remained far superior to that of conventional processes that did not employ this method.

[0052] This embodiment demonstrates that under extreme conditions of high-density furnace loading, this process method effectively compensates for the thermal lag and temperature field unevenness caused by dense furnace loading by extending the low-temperature pre-aging and medium-temperature main aging time, fine-tuning the main aging temperature, and dynamically adjusting the heating and cooling rates at each stage, thus ensuring the performance uniformity of the entire furnace product.

[0053] Comparative Example 1

[0054] This comparative embodiment uses the exact same profiles, equipment, and furnace charge density coefficient as Embodiments 1 and 2, i.e., ρ=0.31, which is at the medium-density furnace charge level. However, the three-stage dynamic process of this invention is not used during heat treatment; instead, the industry-standard single-stage T5 aging regime is used as a control.

[0055] After loading this batch of profiles into the aging furnace, they were directly heated to 180℃ at a conventional heating rate of 3.5℃ / min, and held at 180℃ for 5.5 hours. After the holding period, the heating power was cut off, and the furnace door was opened for natural cooling. This process does not differentiate between loading densities, nor does it subject any special control over the heating and cooling rates.

[0056] After aging treatment, samples were taken from nine locations in the same furnace batch using the same method as in Example 1, and their mechanical properties were tested. The results showed that the tensile strength at the nine locations ranged from 225 MPa to 248 MPa, with a range of 23 MPa; the specified plastic elongation strength ranged from 198 MPa to 221 MPa, with a range of 23 MPa; and the elongation after fracture ranged from 9.2% to 13.1%. Among these, some samples located in the corners or densely populated central areas of the furnace showed lower strength and more dispersed elongation.

[0057] Comparative analysis shows that, under the same furnace charge density conditions, the mechanical property uniformity of Example 1 of this invention is significantly better than that of the single-stage aging process in Comparative Example 1. Single-stage aging, because it does not consider the influence of furnace charge density on the thermal field, results in large differences in the actual thermal history experienced by all profiles, making performance fluctuations difficult to control. In contrast, the method of this invention, by measuring the furnace charge density level and dynamically matching the three-stage aging parameters, especially the precise control of the heating and cooling rates, effectively offsets the influence of uneven thermal field, achieving uniform precipitation.

[0058] The present invention also constructed another set of comparative embodiments to further verify the linkage of process parameters. Under the condition of high-density furnace loading with ρ of 0.50, the process parameters of low-density furnace loading were incorrectly called for production, namely, the first stage of holding at 90℃ for 5.0h, the second stage of holding at 160℃ for 3.0h, and the third stage of holding at 185℃ for 12min.

[0059] The performance test results after treatment showed that the tensile strength range at the nine sampling points was as high as 35 MPa, with strength at many points far below the standard requirements. The specified plastic elongation strength range exceeded 40 MPa, and the elongation after fracture was also extremely uneven. This demonstrates, from the opposite perspective, that applying fixed parameters without considering the furnace charge density coefficient, especially when the furnace charge density is mismatched with the parameter level, will lead to serious deterioration of product performance. Correct parameter linkage is the core of this technical solution in achieving its inventive purpose.

[0060] To more intuitively demonstrate the results of the above embodiments and comparative embodiments, the relevant process parameters and performance data are summarized in Table 1.

[0061] Table 1 shows a comparison of process parameters and performance between different embodiments and comparative embodiments:

[0062] Example 1 0.31 middle 95℃ / 6.0h / 2.0℃ / min 158℃ / 3.5h / 0.8℃ / min 185℃ / 15min / 1.2℃ / min 1.2℃ / min 7 7 Example 2 0.50 high 100℃ / 7.5h / 1.8℃ / min 155℃ / 4.5h / 0.7℃ / min 185℃ / 18min / 1.0℃ / min 1.0℃ / min 11 13 Comparative Example 1 0.31 middle 180℃ / 5.5h / 3.5℃ / min — — Cooling with the furnace 23 23 Comparative Example 2 0.50 high 90℃ / 5.0h / 2.0℃ / min 160℃ / 3.0h / 0.8℃ / min 185℃ / 12min / 1.2℃ / min 1.2℃ / min 35 >40

[0063] As shown in Table 1, the embodiments of the present invention, by dividing the furnace loading density into different levels and formulating a three-stage synergistic process including temperature, time, and heating / cooling rates for each level, confine the range of mechanical properties within the same batch to a very small range. In contrast, single-stage aging that ignores furnace loading density or two-stage aging with parameter mismatch results in performance differences several times greater than the scheme of the present invention, with significantly deteriorated uniformity. This clearly demonstrates that the positive or negative correlation between the furnace loading density coefficient and the three-stage process parameters established in the technical solution of the present invention is key to solving the problem of batch-to-batch performance fluctuations in thin-walled aluminum alloy photovoltaic frames, and its technical effect can be objectively verified by the above experimental data.

[0064] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.

Claims

1. A two-stage aging process for thin-walled aluminum alloy photovoltaic frames, characterized in that, The method includes the following steps: Step 1: Measure the furnace charge density coefficient ρ. ,in L is the sum of the projected areas of all thin-walled aluminum alloy photovoltaic frame profiles in the aging furnace on a plane perpendicular to the length of the furnace chamber, where L is the effective length of the furnace chamber, W is the effective width of the furnace chamber, and H is the effective height of the furnace chamber. Step 2: Based on the charging density coefficient ρ, the charging state is divided into three levels: low-density charging, medium-density charging, and high-density charging. ρ≤0.30 is low-density charging, 0.30<ρ≤0.48 is medium-density charging, and ρ>0.48 is high-density charging. Step 3: Determine the three-stage aging process parameters based on the furnace loading status level. The three-stage aging process includes the first stage of low-temperature pre-aging, the second stage of medium-temperature main aging, and the third stage of short-time regression. The temperature and time of the first stage of low-temperature pre-aging are positively correlated with the furnace loading density coefficient ρ. The temperature and time of the second stage of medium-temperature main aging are negatively correlated with the furnace loading density coefficient ρ, and positively correlated with the furnace loading density coefficient ρ. The temperature of the third stage of short-time regression is 180-190℃, and the time is positively correlated with the furnace loading density coefficient ρ and does not exceed 22 minutes. Step four: Perform a three-stage aging treatment on the thin-walled aluminum alloy photovoltaic frame profile according to the determined process parameters.

2. The method for a two-stage aging process of a thin-walled aluminum alloy photovoltaic frame according to claim 1, characterized in that, In step two, the process parameters for low-density loading are: first stage temperature 90℃, time 5.0h, second stage temperature 160℃, time 3.0h, and third stage temperature 185℃, time 12min. The process parameters for medium-density loading are: first stage temperature 95℃, time 6.0h, second stage temperature 158℃, time 3.5h, and third stage temperature 185℃, time 15min. The process parameters for high-density furnace loading are as follows: first stage temperature 100℃, time 7.5h; second stage temperature 155℃, time 4.5h; third stage temperature 185℃, time 18min.

3. The method for a two-stage aging process of a thin-walled aluminum alloy photovoltaic frame according to claim 1, characterized in that, In step two, the temperature of the first stage low-temperature pre-aging is 80-105℃ and the time is 4-8h, and the temperature of the second stage medium-temperature main aging is 150-168℃ and the time is 2.5-5h.

4. The method for a two-stage aging process of a thin-walled aluminum alloy photovoltaic frame according to claim 1, characterized in that, In step two, the heating rate of the first stage low-temperature pre-aging is 1.5-2.5℃ / min, and the heating rate of the first stage low-temperature pre-aging is negatively correlated with the furnace loading density coefficient ρ.

5. The method for a two-stage aging process of a thin-walled aluminum alloy photovoltaic frame according to claim 1, characterized in that, In step two, the first-stage heating rate between the first-stage low-temperature pre-aging and the second-stage medium-temperature main aging is 0.5-1.2℃ / min, and the first-stage heating rate is negatively correlated with the furnace loading density coefficient ρ.

6. The method for a two-stage aging process of a thin-walled aluminum alloy photovoltaic frame according to claim 1, characterized in that, In step two, the second-stage heating rate between the second-stage medium-temperature main aging and the third-stage short-time regression is 0.8-1.5℃ / min, and the second-stage heating rate is negatively correlated with the furnace loading density coefficient ρ.

7. The method for a two-stage aging process of a thin-walled aluminum alloy photovoltaic frame according to claim 1, characterized in that, In step two, after the short-term regression of the third stage, the temperature is reduced to below 100℃ at a cooling rate of 0.5-1.8℃ / min. The cooling rate is negatively correlated with the furnace density coefficient ρ.

8. The method for a two-stage aging process of a thin-walled aluminum alloy photovoltaic frame according to claim 1, characterized in that, In step one, the furnace loading density coefficient ρ is automatically calculated by the control system after scanning the profile outline by an optical ranging sensor array.

9. The method for a two-stage aging process of a thin-walled aluminum alloy photovoltaic frame according to claim 1, characterized in that, In step one, the furnace loading density coefficient ρ is calculated by the control system after the number of profiles, the cross-sectional outline size of a single profile, and the effective size of the furnace are manually input.

10. The method for a two-stage aging process of a thin-walled aluminum alloy photovoltaic frame according to claim 1, characterized in that, In step one, the wall thickness of the thin-walled aluminum alloy photovoltaic frame profile is 0.8-2.5mm, and the material of the thin-walled aluminum alloy photovoltaic frame profile is 6-series aluminum alloy.

Citation Information

Patent Citations

  • Production process of hard aluminum alloy profiles

    CN102825092A

  • An aluminum alloy heat treatment process

    CN106756669B